1:2‐sequence‐regulated radical copolymerization of naturally occurring terpenes with maleimide derivatives in fluorinated alcohol. Issue 8 (6th February 2013) - Matsuda, Masaru; Satoh, Kotaro; Kamigaito, Masami
Abstract Naturally occurring bulky terpenes, such as (+)‐ and (–)‐limonene and (–)‐β‐pinene, were quantitatively copolymerized with maleimide (MI) derivatives (i.e., phenyl‐, cyclohexyl‐, ethyl‐, and unsubstituted‐MI) in PhC(CF3)2OH solvent via selective 1:2‐alternating propagation governed by the penultimate effect, which resulted in 1:2‐sequence regulated polymers with relatively high glass transition temperatures and optical activities. Similar petroleum‐derived bulky olefins possessing cyclohexenyl, cyclohexyl, or additional α‐methyl substituents were copolymerized with phenylmaleimide via preferential 1:2‐alternating propagation with a slightly lower selectivity. A further decrease in the bulkiness of nonpolar olefins increased the 1:1‐alternating sequence. The copolymerization of limonene and acrylonitrile also proceeded approximately via 1:1‐alternating propagation, in which the penultimate effect was less observable. Furthermore, when methylene chloride was used instead of fluorinated alcohol for the copolymerization of limonene and phenylmaleimide, the length of the sequence of MI units increased. Thus, in addition to the characteristic MI skeleton, the bulky and rather specific structure of either limonene or β‐pinene induces 1:2‐selective propagation via the penultimate effect, whereas the fluoroalcohol diminishes the homopropagation of MI via a hydrogen bonding interaction with the MI unit. RAFT copolymerization of limonene and various MI derivatives in PhC(CF3)2OH successfully proceeded to give the end‐to‐end 1:2‐sequence‐regulated copolymer with a selective initiating sequence and predominant capping sequence using an appropriate RAFT agent. © 2013 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem, 2013